(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Article is devoted to the problem of the study of artistic originality and poetic interpretation of women’s fate in the lyrics B.Grinchenko . Female character is the semantic center of a number of works of the poet. Social and psychological aspects of the character representation of women in the lyrical character , through the lyrical "I" , the lyrical hero, hero "role " of the lyrics . Considerable attention is paid to the specifics of the reflection period in the author’s artistic conception of a woman